مدى تطبيق عناصر الجودة في الخدمات المصرفية كمدخل لتحقيق الميزة التنافسية دراسة على المصارف التجارية الاردنية - القضاه, محمد ناجيد (Recherches économiques et managériales; Vol. 19 (2016): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (JUIN), 2016)
تهدف هذه الدراسة إلى معرفة مدى تطبيق عناصر الجودة في تحقيق الميزة التنافسية في المصارف التجارية الأردنية، وتقرير ما اذا كانت هناك علاقة ذات دلالة إحصائية بين عناصر الجودة واستراتيجيات الميزة التنافسية في المصارف التجارية، بالإضافة الى التأكد من وجود تأثير معنوي لعناصر المتغيرات المستقلة (التخطيط الاستراتيجي، ورضا العملاء، وكفاءة القوى العاملة) على المتغيرات التابعه للميزة  التنافسية (استراتيجية المنافسة في قيادة التكاليف، واستراتيجية المنافسة في التميز والتنويع) في المصارف التجارية الأردنية ولتحقيق هدف الدراسة، فقد تم تحديد مجتمع الدراسة من موظفي الادارة العليا والوسطى ومديري فروع المصارف التجارية الاردنية، يتكون مجتمع الدراسة والبالغ عددها( 6) مصارف تجارية، أما العينة فقد تم اخذ عينة عشوائية طبقية ممثله في كل مصرف،وقد تم تطبيق الأساليب الإحصائية بما يتناسب مع طبيعة بيانات الدراسة وذلك من خلال استخدام البرنامج الإحصائي (SPSS) و(Minitab). وتوصلت الدراسة إلى النتائج التالية: 1-    هناك علاقة ذات دلالة إحصائية بين كل من: التخطيط الاستراتيجي، رضا العملاء واستراتيجية المنافسة بالتميز والتنويع، بينما لا توجد علاقة ذات دلالة إحصائية بين هذه العناصر واستراتيجية المنافسة بقيادة التكاليف. 2-    هناك تطبيق للتخطيط الاستراتيجي، وكفاءة القوى العاملة في المصارف التجارية 3-    هنالك اعتمادية بين عناصر الجودة واستراتيجية المنافسة بالتميز والتنويع حيث نلاحظ ان كل من التخطيط الاستراتيجي، ورضا العملاء وكفاءة القوى العاملة غير مستقلة عن استراتيجية المنافسة بالتميز والتنويع. 4-    لا توجد علاقة ذات دلالة إحصائية بين كفاءة القوى العاملة واستراتيجيات الميزة التنافسية ( المنافسة بقيادة التكاليف والمنافسة بالتميز والتنويع). 5-    هنالك تأثير معنوي لعنصر الجودة رضا العملاء على المتغير التابع ( الميزة التنافسية). بينما لا يوجد تأثير معنوي لكل من عنصري الجودة المستقلة هما التخطيط الاستراتيجي وكفاءة القوى العاملة على المتغير التابع (الميزة التنافسية). الكلمات المفتاحية: الخدمات المصرفية، عناصر الجودة، استراتيجيات الميزة التنافسية، المصارف التجارية Abstract This study aims to find out how the application of quality elements to achieve competitive advantage in the Jordanian commercial banks, and determine whether there were statistically significant differences between the quality elements and strategies for competitive advantage in commercial banks keep a relationship, as well as to ensure that there is a significant effect of the independent variables (strategic planning, customer satisfaction, workforce) on the dependent variables of competitive advantage (competition strategy to led by the costs ,competitive strategy to excellence and diversification) at the Jordanian commercial banks  To achieve the objective of the study, have been identified study population consisted of senior and middle management staff and managers of the branches of Jordanian commercial banks, made up the study population of (6) commercial banks, and the sample has been taken stratified random sample representative at the bank.        The application of statistical methods in proportion to the nature of the study and data through the use of statistical program Statistical Package for Social Science) (SPSS) and (Minitab). The finding of this study indicate the following: 1- There was statistically significant relationship between: strategic planning, customer satisfaction and competitive strategy to excellence and diversification, while there is no statistically significant relationship between these elements and competition strategy, led by the costs. 2- There is an application for strategic planning, and efficient workforce in commercial banks 3- There is reliability between elements of quality and competitive advantage strategies where we note that all of the strategic planning, customer satisfaction and efficiency of the workforce is independent of competition to excellence and diversification strategy 4- There are no statistically significant relationship between the workforce and the efficiency of all strategies for competitive advantage (competition costs and competition led to excellence and diversification) 5- There is a significant effect of component quality customer satisfaction on the dependent variable of competitive advantage. While there is no significant effect for each of the two components of the independent quality of strategic planning and the efficiency of the work force on the dependent variable (competitive advantage). Key words : banking services, quality elements, strategies of competitive advantage, commercial banks